Coping with breast cancer together: Challenging topics for mothers and their adolescent-young adult (AYA) daughters. Issue 6 (2nd November 2022) - Fisher, Carla L.; Kastrinos, Amanda; Piemonte, Nicole; Canzona, Mollie R.; Wolf, Bianca; Pipe, Teri
Abstract: Background. The mother-daughter relationship can be central to women who are coping with breast cancer and provide a key source of support. However, the adolescent and young adult (AYA) daughters of diagnosed mothers have been known to exhibit notable distress during this time, withdrawing and avoiding communication, further challenging their ability to cope together. Objective. We sought to identify challenging topics that contribute to this avoidant mother–daughter communication pattern, as a first step in helping mothers and AYA daughters facilitate health-promoting communication. Methods. We examined thematically analyzed transcripts of one-on-one, in-depth, semi-structured interviews with 27 women (12 mother–daughter dyads). Results. We to identified 3 broad topics that were challenging to discuss: daughters' future breast cancer risk; emotionally related concerns; and clinical and physical aspects of disease. Thematic properties illustrate the challenging nature of each topic that informed their ability to communally cope together. Implications. Findings provide an initial roadmap for developing communication skills interventions that help mothers and AYA daughters navigate challenging conversations and facilitate communal coping.